Cetacean Orbital Muscles: Anatomy and Function of the Circular Layers. Issue 7 (13th November 2019) - Meshida, Keiko; Lin, Stephen; Domning, Daryl P.; Reidenberg, Joy S.; Wang, Paul; Gilland, Edwin
ABSTRACT: Dissections of cetacean orbits identified two distinct circular muscle layers that are uniquely more elaborate than the orbitalis muscles described in numerous mammals. The circular orbital muscles in cetaceans form layers that lie both external and internal to the rectus extra ocular muscles (EOMs). A cone‐shaped external circular muscle (ECM) that invests the external surface of the rectus EOMs was found in all cetacean specimens examined. The cetacean ECM corresponds generally to descriptions of the musculus orbitalis in various mammals but is more strongly developed and has more layers than in noncetaceans. A newly identified internal circular muscle (ICM) is located internal to the rectus EOMs and external to the retractor bulbi (RB). The RB is massive in cetaceans and is encased in a connective tissue layer containing convoluted bundles of blood vessels. The most robust ECM and ICM layers were in sperm whale ( Physeter macrocephalus ) where they form complete rings. Surprisingly, histological analysis showed the sperm whale ECM to contain both smooth and striated (skeletal) muscle layers while the ICM appeared to contain solely skeletal muscle fibers. The extreme development of the ECM (orbitalis) and RB suggest a co‐evolved system mediating high degrees of protrusion and retraction in cetaceans. We know of no homolog of the ICM but its function seems likely related to the complex vascular structures surrounding and deep to the retractor muscle. Skeletal muscle components in orbital circular muscles appear to be highly derived specializations unknown outside of cetaceans. Anat Rec, 2019. © 2019 American Association for Anatomy Anat Rec, 303:1792–1811, 2020. © 2019 American Association for Anatomy